Solución digital para el dimensionamiento de facilidades de almacenamiento estratégico en la red de poliductos de Colombia (2024)
The development and implementation of a digital tool for the sizing of strategic storage facilities in the Colombian pipeline network arises from the need to optimize processes based on data processing. The company CENIT | Hydrocarbon Transportation and Logistics is in charge of managing and adapting the pipeline system to the country's growing demand for liquid fuels. A database corresponding to inventory levels in liquid fuel storage plants was generated, with which a code was developed to size new storage facilities according to the capacity needs in the system. The digital solution was made with the Java SE language. Subsequently, the sizing was validated by comparing the result against the expected real value, in the plant selected for study.